2007
DOI: 10.21608/jppp.2007.220163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irradiation on Plant Growth and Some Pests Incidence In: Cotton and Kidney Beans

Abstract: The effects of low doses of gamma irradiation on cotton, Gossypium barbadence kidney beans, Phasolus vulgaris were investigated. Seeds for each crop were irradiated with 4 doses of gamma radiation, 15, 25, 35 and 45 Kilo rad for cotton and 5, 10, 20 and 30 Kilo rad for kidney beans. Plants of the two crops were used to determine growth parameter. Since, kidney beans plants were negatively affected in the most of its growth parameter as a result of gamma radiation, and cotton plants were highly affected and cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many researchers observed that gamma irradiation causes significant changes in pest biology concerning reproduction; irradiation at low irradiation doses eliminated most Alternaria, Fusarium, leafhopper, cotton leaf worm and two-spotted spider mite (Megali, 1987;Hussein et al, 1999;Ramakrishna et al, 1991;Abdu El-Nour and Ibrahim, 2006and Hussein et al, 2005and 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers observed that gamma irradiation causes significant changes in pest biology concerning reproduction; irradiation at low irradiation doses eliminated most Alternaria, Fusarium, leafhopper, cotton leaf worm and two-spotted spider mite (Megali, 1987;Hussein et al, 1999;Ramakrishna et al, 1991;Abdu El-Nour and Ibrahim, 2006and Hussein et al, 2005and 2007.…”
Section: Introductionmentioning
confidence: 99%